Broadband Polarization Beam Splitter by Using Cascaded Tapered Bent Directional Couplers - Ning Zhao; Ciyuan Qiu; Yu He; Yong Zhang; Yikai Su (IEEE Photonics Journal)
We propose and demonstrate a broadband silicon-based polarization beam splitter (PBS) by using cascaded tapered bent directional couplers (DCs). In our device, the TM-polarized light is efficiently cross coupled to the cross port due to the strong coupling in the DCs, while the TE-polarized light goes through the DC with weak coupling and outputs at the through port. This device can achieve a broad bandwidth performance and support O-, S-, C-, and L-band operations, with acceptable extinction ratios (ERs) and insertion losses (ILs). For both TE and TM polarizations, the simulation results show that ERs are ≥10.1 dB and ILs are ≤1.33 dB in 1280–1600 nm. In the measurement, for the TE polarization, an ER ≥10.94 dB and an IL ≤1.61 dB are obtained in 1280–1360 nm, while an ER ≥11.98 dB and an IL ≤1.39 dB are measured in 1510–1590 nm. For the TM polarization, an ER ≥12.25 dB and an IL ≤2.22 dB are obtained in 1280–1360 nm, while an ER ≥18.93 dB and an IL ≤1.22 dB are measured in 1510–1590 nm.